2014
DOI: 10.1111/srt.12164
|View full text |Cite
|
Sign up to set email alerts
|

Patients with tattoo reactions have reduced quality of life and suffer from itch

Abstract: Sufferers of tattoo reactions have reduced quality of life and are often burdened by itching attaining the level of other cumbersome afflictions recognized as dermatological diseases associated with itch. Tattoo reactions warrant diagnosis and treatment with same professional intent shared with other skin diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Although permanent makeup is common and regarded safe, it may still cause adverse skin reactions, including infections, allergic reactions, and autoimmune diseases such as sarcoidosis. Regardless of the size of the affected area, tattoo reactions cause a reduced quality of life …”
Section: Five Cases Of Granulomatous Reactions In Permanent Makeupmentioning
confidence: 99%
“…Although permanent makeup is common and regarded safe, it may still cause adverse skin reactions, including infections, allergic reactions, and autoimmune diseases such as sarcoidosis. Regardless of the size of the affected area, tattoo reactions cause a reduced quality of life …”
Section: Five Cases Of Granulomatous Reactions In Permanent Makeupmentioning
confidence: 99%
“…The reactions have a range of clinical manifestations and possible mechanisms, with infection and suspected allergy being prominent. Chronic reactions are associated with fiery itching and a reduced quality of life, in line with other chronic dermatoses . In a recent review, Kluger and Koljonen found no risk of cutaneous malignancy associated with the pigments of tattoos .…”
mentioning
confidence: 96%
“…3 Complications of tattoos can also be divided into cutaneous or systemic and can have an impact on the quality of life. 4 Cutaneous complications can occur either immediately or be delayed hypersensitivity reaction to tattoo ink. The infection may be introduced into the skin during the breach of the epidermal barrier.…”
Section: Discussionmentioning
confidence: 99%